ZOUK DANCE: CONTRIBUTION OF FLEXIBILITY IN THE PERFORMANCE (Fiep Bulletin - online, 2016)
The paper's purpose was to relate the influence of body flexibility in the "zouk" dance. It was possible to use as a source of research, sites and researchers publications of this dance modality, in Brazil, and scientific books and articles to look for knowledge about flexibility.  Proficiency maintenance or performance increase is given by training continuity to raise the aesthetic level of dancing through precision and timing of each body part. The flexitest is a measuring instrument that verifies more succinctly and efficiently the flexibility difference between teachers and students. The research was carried out with four teachers and four students, all of them practitioners of "zouk" style. They were submitted to three flexitest positions about the spine: trunk flexion, trunk extension and trunk lateral flexion. The test was performed with and without warming-up, and the study data showed the greatest level of flexibility in the teachers group before and after warming-up. However, most of the participants got positive results in the score increase after warming-up. Indicators such as weight, height and BMI showed no direct interference in the paper, unlike the participants' age that according to the literature may have influenced throughout the test. It was possible to use the student t-test to validate the results. The values were significant in all analyzes collected, taking as a reference the standard value (alpha = 0.05), keeping a proof of relation to averages in the performance of students and teachers. Thus, it is possible to conclude that flexibility is vital in the "zouk" dance, and also, it is a trainable valence.
Keywords: Dance. Zouk. Flexibility. Performance.